2010
DOI: 10.1128/cvi.00379-09
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines across the Night in Chronic Fatigue Syndrome with and without Fibromyalgia

Abstract: The symptoms of chronic fatigue syndrome (CFS) are consistent with cytokine dysregulation. This has led to the hypothesis of immune dysregulation as the cause of this illness. To further test this hypothesis, we did repeated blood sampling for cytokines while patients and matched healthy controls slept in the sleep lab. Because no one method for assaying cytokines is acknowledged to be better than another, we assayed for protein in serum, message in peripheral blood lymphocytes (PBLs), and function in resting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 34 publications
3
51
1
2
Order By: Relevance
“…We found that levels of IL-10, an anti-inflammatory cytokine, were significantly higher during nighttime sleep in patients than in matched controls but not during the period prior to sleep (8). We recently completed a large study using multiple methods to assay for cytokines during the sleep of CFS patients with and without FM (9). That study also found increases in nocturnal IL-10 in patients with CFS only but not in patients with both CFS and FM.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…We found that levels of IL-10, an anti-inflammatory cytokine, were significantly higher during nighttime sleep in patients than in matched controls but not during the period prior to sleep (8). We recently completed a large study using multiple methods to assay for cytokines during the sleep of CFS patients with and without FM (9). That study also found increases in nocturnal IL-10 in patients with CFS only but not in patients with both CFS and FM.…”
mentioning
confidence: 68%
“…The subjects then awoke between 7:15 and 8:00 a.m., after which a final blood sample was taken. The sleep and cytokine data from this normal night have been published elsewhere (9).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations